Anti estrogens effect of citrate of tamoxifen on testicular and seminal parameters of male dogs (Veterinary Science, 2017)
The citrate of tamoxifen is a synthetic non steroid type I anti-estrogenic compound, which block competitively estrogens receptors with agonist and antagonist combine action. The mechanism of action varies in relation to species, organs, tissue and cells. The objective of the present study was to describe the macroscopic testicular and seminal epididymis changes in domestic dogs treated with citrate of tamoxifen. Six clinically, 2 - 5 years old healthy dogs between 15 - 25 kg of weigh were analysed. The study included a pretreatment, treatment and post-treatment period of 15, 30 and 45 days, respectively. During the treatment period the animals received 5 mg/day of tamoxifen, and every 15 days clinical examination of testicular consistency and size, libido and epididymal semen were evaluated. ANOVA was used to evaluate quantitative data while the categorical data were evaluated by Chi2. The libido of the animals decreased from the day 15 of the study until the day 75 where start to increase again. The testicular consistency and size decreased from 30 to 60 days, recovering pre-treatment size by day 75 of the study, and at the same time not evidence of epididymis semen were recorded. The percentage of live spermatozoa and motility decreased significantly between treatment days 0 to 30. These clinical testicular and epididymal seminal parameters showed an application of citrate of tamoxifen in male dogs as an effective, sudden and sure method of reversible contraception.
Keywords: Tamoxifen; Anti estrogen; Reproduction; Dog